1998
DOI: 10.1172/jci2680
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-resistant bronchial asthma is associated with increased c-fos expression in monocytes and T lymphocytes.

Abstract: Unstimulated peripheral blood mononuclear cells (PBMCs) from corticosteroid-resistant (CR) but not corticosteroidsensitive (CS) asthmatics demonstrate increased activating peptide-1 (AP-1)-and decreased glucocorticoid receptor (GR)-DNA binding. We test whether these abnormalities are associated with excessive generation of c-fos , the inducible component of AP-1. The c-fos transcription rate, mRNA and protein levels, and GR-DNA binding were quantitated in PBMCs, T cells, and monocytes from CS, CR, and nonasthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 31 publications
0
63
0
3
Order By: Relevance
“…In a subsequent study using nuclear run-on, RT-PCR and Western blotting, we demonstrated a two-to fourfold greater increase in the c-fos transcription rate and mRNA and protein expression in PBMCs isolated from CR compared with CS asthmatics and normal subjects (Lane et al 1998). When cells were stimulated with phorbol 12-myristate 13-acetate (PMA), the time-and concentration-dependent induction of c-Fos was greater in the CR group.…”
Section: Cross-talk With Other Transcription Factorsmentioning
confidence: 85%
“…In a subsequent study using nuclear run-on, RT-PCR and Western blotting, we demonstrated a two-to fourfold greater increase in the c-fos transcription rate and mRNA and protein expression in PBMCs isolated from CR compared with CS asthmatics and normal subjects (Lane et al 1998). When cells were stimulated with phorbol 12-myristate 13-acetate (PMA), the time-and concentration-dependent induction of c-Fos was greater in the CR group.…”
Section: Cross-talk With Other Transcription Factorsmentioning
confidence: 85%
“…Thus, severe asthma that is refractory to treatment with corticosteroids may be associated with the persistent expression of key disease causality and severity genes. Consistent with this concept, dysregulated gene expression has been documented in peripheral blood mononuclear cells and bronchoalveolar lavage cells from corticosteroid-resistant patients with asthma (8)(9)(10). Murine asthma models have also identified corticosteroid-unresponsive genes and the dissociation of airway inflammation from airway hyperreactivity (AHR) and remodeling responses in response to corticosteroid treatment (11)(12)(13).…”
mentioning
confidence: 78%
“…AP-1, a heterodimer of Fos and Jun proteins, is increased in PBMCs and bronchial biopsies of steroid-resistant compared to steroid-sensitive asthma, with no reduction in JNK activity or c-Jun after high doses of oral steroids [94].…”
Section: Mechanisms Of Corticosteroid Insensitivitymentioning
confidence: 97%